Correlation of Principal’s Managerial Abilities and The Work Climate with The Teachers Work Ethos - Dekawati, Ipong; Ruhita, Ruhita; Pujiyati, Wresni; Triwanti, SIS (Universitas Pendidikan Indonesia, 2021)
Abstract-Teacher is a link between the values upheld by the school and the community so that it places work ethic as an important element for teachers to have. Based on preliminary observations it is assumed that teacher's work ethic and principal’s managerial ability are still low, and the work climate is not conducive so that it will affect the achievement of school goals. Therefore, research is needed to test its truth. This study aims to uncover the correlation between the principal's managerial ability and work climate, either partially or simultaneously, with the work ethic of elementary school. This research uses quantitative methods with descriptive - inferential statistical analysis of correlation techniques. Data collection techniques through a Likert scale questionnaire of 43 respondents who are elementary school teachers. The results of data analysis show that (1) the principal's managerial ability correlates with the work ethic of elementary school teacher, (2) Work climate correlates with the work ethic of elementary school teachers, (3) Principal's managerial ability and work climate together correlate with the work ethic of elementary school teachers. The author suggests, that one of the efforts that can be done is by coaching the participants through seminar participation that is not only on a national scale but also internationally. This is done as a means of broadening the insight and educational knowledge of teachers so that they are motivated to see work actions as a competitive process of achieving work. If these conditions can be carried out in a sustainable manner, it can increase the chances of improving the work ethic of teachers.